Synthesis And Characterization Of Silver Or Silver Sulfide Filled Poly(3-Hydroxybutyrate) Nanocomposites - Yeo , Siew Yean (2012)

(untitled)
Ag and Ag2S hydrosols were synthesized via chemical reduction and reflux methods respectively. A simple aqueous to organic phase transfer technique was employed to transfer the Ag and Ag2S nanoparticles from the respective hydrosol into poly(3-hydroxybutyrate) [PHB] chloroform solution. The Ag and Ag2S nanoparticles were stabilized by the PHB polymer in the organosols. The presence of metallic Ag or the Ag2S particles in the newly formed nano-biocomposites were confirmed by the X-ray Diffraction (XRD) technique. The particles size of Ag and Ag2S were within 7-12 nm and 14-24 nm respectively. At low concentration of PHB, the shape of Ag particles was sphere while for Ag2S particles were hexagonal-like.